Hydrodynamics of hydrocyclone with built-in water injector - Minkov, L.; Farghaly, M.; Dueck, J. (Publishing House of the KarSU named after E.A.Buketov, 2011)
The paper considers the numerical simulation of 3D fluid dynamics based on the k-eps RNG model of turbulence in the hydrocyclone with the injector, containing 5 tangentially directed nozzles. The simulation results are supported by experimental research. It is shown that the direction of movement of injected fluid in the hydrocyclone depends on the water flow rate through the injector. Experiments and calculations show that the dependence of the Split-parameter on the injected water flow rate has a non-monotone character associated with the ratio of power of the main flow and the injected fluid.
Keywords: numerical simulation; hydrocyclone; injector; injected fluid; water flow rate; split-paramete